Therapeutic drug monitoring for triazoles: A needs assessment review and recommendations from a Canadian perspective - Michel Laverdiere; Eric J Bow; Coleman Rotstein; Julie Autmizguine; Raewyn Broady; Gary Garber; Shariq Haider; Trana Hussaini; Shahid Husain; Philippe Ovetchkine; Jack T Seki; Yves Théorêt (Canadian Journal of Infectious Diseases and Medical Microbiology)
Invasive fungal infections cause significant morbidity and mortality in patients with concomitant underlying immunosuppressive diseases. The recent addition of new triazoles to the antifungal armamentarium has allowed for extended-spectrum activity and flexibility of administration. Over the years, clinical use has raised concerns about the degree of drug exposure following standard approved drug dosing, questioning the need for therapeutic drug monitoring (TDM). Accordingly, the present guidelines focus on TDM of triazole antifungal agents. A review of the rationale for triazole TDM, the targeted patient populations and available laboratory methods, as well as practical recommendations based on current evidence from an extended literature review are provided in the present document.